Impact of diabetes mellitus on clinical parameters and treatment outcomes of newly diagnosed pulmonary tuberculosis patients in Thailand. Issue 11 (10th June 2013) - Duangrithi, D.; Thanachartwet, V.; Desakorn, V.; Jitruckthai, P.; Phojanamongkolkij, K.; Rienthong, S.; Chuchottaworn, C.; Pitisuttithum, P.
Summary: Background: To assess the clinical and laboratory parameters, response to therapy and development of antituberculosis (TB) drug resistance in pulmonary TB (PTB) patients with diabetes mellitus (DM) and without DM. Methods: Using a prospective design, 227 of 310 new cases of culture‐positive PTB diagnosed at the Queen Savang Vadhana Memorial Hospital and the Chonburi Hospital between April 2010 and July 2012 that met the study criteria were selected. Data regarding clinical and laboratory parameters, drug susceptibility and treatment outcomes were compared between PTB patients with DM and those without DM. To control for age, the patients were stratified into two age groups (< 50 and ≥ 50 years) and their data were analysed. Results: Of the 227 patients, 37 (16.3%) had DM, of which 26 (70.3%) had been diagnosed with DM prior to PTB diagnosis and 11 (29.7%) had developed DM at PTB diagnosis. After controlling for age, no significant differences were found between the two groups regarding mycobacterium burden, sputum‐culture conversion rate, evidence of multidrug‐resistant tuberculosis, frequency of adverse drug events from anti‐TB medications, treatment outcomes and relapse rate. The presenting symptoms of anorexia (p = 0.050) and haemoptysis (p = 0.036) were observed significantly more frequently in PTB patients with DM, while the presenting symptom of cough was observed significantly more frequently in PTB patients without DM (p = 0.047). Conclusions: Plasma glucose levels should be monitored in all newly diagnosed PTB patients and a similar treatment regimen should be prescribed to PTB patients with DM and those without DM in high TB‐burden countries.